Past perceptions and future expectations: Sensed dis/continuity at the start of teacher education. (August 2016) - van Rijswijk, M.; Akkerman, Sanne F.; Schaap, Harmen; van Tartwijk, Jan
Abstract: Because of pressing issues such as teacher attrition, we explored differences in student teachers' expectations and perceptions as they entered teacher education. Thirty-five narrated self-concepts of student teachers in a post-graduate teacher education program were studied. From these we identified four types of past perceptions and four types of future expectations. Combinations of perceptions and expectations were found to be illustrative of three types of sensed dis/continuity in student teachers. The findings assemble into a framework that can be beneficial for researchers and teacher educators in diagnosing dis/continuities in the self-concept and consequent expectations about further development as a teacher. Highlights: Self-concepts of student teachers include a large variety of characteristics. Their sense of (dis)continuity shows variance in professional identification. The framework of (dis)continuity can be beneficial for adaptive supervision.